Pains and portends: A collaborative autoethnography of engineering faculty navigating gendered cultures - Miller, Callie A.; Castaneda, Daniel I.; Alemán, Melissa Wood (Frontiers in Communication, 2023)
This mediated collaborative autoethnography uses reproduced dialogue, poetic inquiry, and composite, fictionalized narratives to story the gendered experiences of two instructional faculty teaching a coordinated engineering class and working in an undergraduate engineering program at a large public university. The contrasting, gendered narratives of the engineering faculty storied in this paper illuminate several themes: (1) discourses of gendered relational labor (masculinized savior vs. feminized emotional work); (2) gendered experiences of invisibility (not being heard or recognized for expertise) and hypervisibility (as a woman in engineering); and (3) the discounting and attempted diminishment of gendered issues in organizational settings. While self-reflexive and dialogic practices embodied in this autoethnography reveal the transformative possibility of accomplices in disrupting gendered relations of power and activating social change from within, those practices alone are insufficient to trouble the masculine culture of engineering. Authentic change demands that these practices be joined with structural, organizational changes in order to reconcile disparate, gendered experiences in engineering cultures, lest the exodus of women from masculine-dominant engineering fields persist unabated.